Making Meaning of Justice Ideals for Intimate Partner Violence: reflections on Restorative Justice - Ehret, Stephanie (The British journal of criminology, 2020)
This is an examination of Barbara Hudson's theory of social justice and her delineation of three principles at the centre of restorative justice—discursiveness, reflectiveness and relationalism. It explores how justice might be done for intimate partner violence (IPV) through the principles. Part of a larger project, this study consists of critically informed one-on-one interviews with 12 women who have experienced IPV. It finds the women conceptualize justice socially and reconfigure and relocate the principles to prioritize social collaborations and protective solutions in extralegal locations with persons who understand the complexities and challenges of the issue.